2011
DOI: 10.1557/opl.2011.847
|View full text |Cite
|
Sign up to set email alerts
|

Development of lead-free materials for piezoelectric energy harvesting

Abstract: Mechanical energy harvesting from ambient vibrations is an attractive renewable source of energy for various applications. Prior research was solely based on lead-containing materials which are detrimental to the environment and health. Therefore, lead-free materials are becoming more attractive for harvesting applications. The present work is focused on the development of lead-free piezoelectric materials based on solid solution having composition (KNa)NbO 3 -xABO 3 , (where A = Li, and B = Nb; x = 0, 5, 5.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Since PZT contains lead that might have potential health issues, there is a strong drive to investigate alternative materials. Rai et al [95] discuss finding lead-free materials, with one example being shown in (figure 39). Attempts have been made to produce efficient lead-free piezoelectric materials.…”
Section: Pb Free Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since PZT contains lead that might have potential health issues, there is a strong drive to investigate alternative materials. Rai et al [95] discuss finding lead-free materials, with one example being shown in (figure 39). Attempts have been made to produce efficient lead-free piezoelectric materials.…”
Section: Pb Free Materialsmentioning
confidence: 99%
“…Single-phase formation and good crystallinity with LiNbO 3 addition up to x = 6.5 wt% were reported. Dielectric studies reveal that the composition with LiNbO 3 = 6.5 wt% exhibits properties suitable for piezoelectric energy-harvesting applications [95].…”
Section: Pb Free Materialsmentioning
confidence: 99%
“…However, this harvester was fabricated merely by cutting mechanically the Si wafer on which the KNN film was deposited. A practical application of the KNN film to the micromachined structure has not been reported yet [8,9]. In this study, a lead-free KNN-based energy harvester was fabricated using bulk micromachining and verified experimentally.…”
Section: Introductionmentioning
confidence: 98%
“…18,19) However, a practical application of the KNN film to the micromachined structure has not been adequately reported. [18][19][20] In this study, a fully micromachined energy harvester employing the KNN film and nonlinear feature of the clamped-clamped beam was fabricated and evaluated.…”
Section: Introductionmentioning
confidence: 99%